(untitled) (The Research of Medical Science Review, 2024)
This analysis will analyze the growing concern of pollution, including smog, and its expected impacts on human and animal health. With the increasing urbanization and industrialization worldwide, air pollution is expected to rise, resulting in considerable health issues. This review aims to summarize existing data on the health effects of smog, emphasizing its implications for respiratory and cardiovascular disorders and mental health concerns. Research will demonstrate that prolonged exposure to air pollutants, especially fine particulate matter (PM2.5), correlates with heightened morbidity and mortality rates in humans and animals. Research indicates that children subjected to elevated air pollution levels would suffer from compromised lung development, whereas adults will encounter increased chances of chronic respiratory ailments and cardiovascular disorders. The review will emphasize the psychological impacts of air pollution, indicating that smog contributes to depression and anxiety, especially among vulnerable groups. The process will thoroughly examine peer-reviewed articles and studies that detail the health impacts of air pollution across diverse demographics and geographical areas. Essential findings will demonstrate that the impression of air quality markedly affects mental health outcomes, with persons residing in heavily polluted regions indicating diminished levels of pleasure and life satisfaction. The study will conclude by underscoring the pressing necessity for public health interventions and governmental initiatives to mitigate air pollution. Additional research will also be necessary to investigate the long-term health consequences of smog and devise effective measures for alleviating its effects on human and animal health.